The Effect of Inclusion of Lime as Acidifier in Step-Down Feeding System on Intestinal Condition of Broiler Chickens - . Jamilah; N. Suthama; L. D. Mahfudz (Fakultas Peternakan, Universitas Hasanuddin, Makassar, 2014)
The aim of the research was to improve the condition of the broilers’ intestine raised with single step down feeding system and the dietary inclusion of lime as acidifier. The research was conducted based on the completely randomized design with 8 treatments and 4 replication (consisted of 8 broiler each). Treatments were P0 (normal diet), P1 (single step down diet), P2 (single step down diet + citric acid 0.8%), P3 (single step down diet + lime acid 0.4 % (6.9 ml / 100g feed)) P4, (single step down diet + lime acid 0.8% (13.8 ml / 100g feed)) and P5 (single step down diet + lime acid 1.2% ( 20.7 ml / 100g feed)). Weight and length of the villi of all part of the small intestine were not affected by the addition of lime, but villi height of the duodenum was significantly affected by the inclusion of lime in the diet. Single step down feeding system and dietary inclusion of lime improve duodenal villi characteristic of broiler chickens.